Construcción de maquinaria de acondicionamiento físico aplicando procesos de soldadura mig/mag en el bloque b de la Universidad Técnica de Cotopaxi extensión La Maná, año 2015 - Pilaguano Ayala, Edison Hernán (2015)
Industries have the need to use high-quality materials, safe and long lasting, welding parts involved in the metal mechanical area are a fundamental part in the development of industrial projects, pipeline systems, automotive, automation, among others applications where welding must have high quality parameters to pass acceptance and inspection.